Position: A study protocol for the prevention of fall injuries in french special forces selection courses using a body-centered intervention. - Loucas Obligi; Mathieu Bertrand; Mathieu Boivent; Simon-Pierre Corcostegui; Pierre-Emmanuel Coz; Clément Derkenne; Vincent Des Robert; Victor Hurpin; Jauffrey Hus; Benoît L'Hermitte; Laurent Lely; Edouard Patey; et al. (PLoS ONE, 2023)
Introduction The Military Physical and Sports Training program was developed by the French Army in order to train, optimize, and maintain individual readiness. Although the health benefits of sport practice do not need to be demonstrated, such activities can cause acute musculoskeletal injuries that need to be addressed. The prevalence of lower limb injury is rather high in the French military population and, in particular, ranges from 15 to 45% during Special Forces selection courses. Thus, this project aims to investigate the efficiency of a body-centered program designed to enhance body awareness. The program seeks to train the mind to actively pay attention to body information, while the latter is viewed as a protective factor against fall injuries. We assume: (i) that postural control can be improved by enhancing the level of body awareness; and (ii) that greater postural awareness could be beneficial in reducing the risk of fall injuries. The body-centered prevention program is based on the Optimization of the Resources of the Armed Forces (ORAF) intervention, which focuses on mental preparation and recovery, and has been deployed in the French Army for many years. Method and analyses The study focuses on five French Special Forces selection courses (400 soldiers/ participants). It is divided into two stages (year 1, year 2). The first year is dedicated to data collection from the control group (200 participants), while in the second year the ORAF intervention will be deployed. In both year, participants will be subjected to the same enrollment schedule (Fig 3). The main objective is to evaluate the effectiveness of the ORAF intervention in reducing the rate of fall injuries during military selection, based on a multidisciplinary method that captures demographic, biological, biometric, clinical, and para-clinical measures. Trial registration Registration number: IDRCB number 2021-A02108-33, Clinical Trial: NCT05451394.